1972
DOI: 10.1111/j.1423-0410.1972.tb04645.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Ferritin‐Labelled Antibodies Bound to Human Erythrocytes Fixed with Glutaraldehyde1

Abstract: Summary In this immuno‐electron microscopic study, the capability of the combining antibody and the agglutinability was examined in glutaraldehyde‐fixed erythrocytes. Glutaraldehyde‐fixed human red cells preserved a strong ability to bind specific antibodies as unfixed cells, even though they decrease in agglutinability. As the fixed cells were separated from one another, even when were agglutinating, the localization of antibodies on a cell in the fixed cells was very clear. The number of A antigen sites per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Labelling pattern. The surface staining always appeared as a continuous layer of dense reaction, and differed from that obtained by others with ferritin-conjugated reagents (Lee & Feldman, 1964;Matsukura, 1972;Voak & Williams, 1971;Williams& Voak, 1972). In these latter experiments, ferritin molecules are distributed in a discontinuous pattern, suggesting a periodic distribution of antigen sites which lends to quantitative estimations.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Labelling pattern. The surface staining always appeared as a continuous layer of dense reaction, and differed from that obtained by others with ferritin-conjugated reagents (Lee & Feldman, 1964;Matsukura, 1972;Voak & Williams, 1971;Williams& Voak, 1972). In these latter experiments, ferritin molecules are distributed in a discontinuous pattern, suggesting a periodic distribution of antigen sites which lends to quantitative estimations.…”
Section: Discussionmentioning
confidence: 54%
“…In addition such variations have already been reported by several workers using the immunofluorescence method (Cohen & Zuelzer, 1965;Fischer & Stege, 1967;Poskitt et ul, 1974;Reed, 1964) or sophisticated immunoadherence techniques (Poskitt & Fortwengler, 1974). Some differences in surface labelling were also noted without comment in recent immunoelectron microscopic experiments using ferritin-conjugated antibodies (Voak & Williams, 1971;Matsukura, 1972).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The binding of anti-A antibodies to erythrocytes has been studied previously in immunofluorescence (1, 2), transmission electron microscopy (3)(4)(5)(6) and in scanning electron microscopy (SEM) (7). Both polyclonal (1)(2)(3)(4)(5)(6) and mouse monoclonal anti-A (7) have been investigated. These studies have revealed that amount and composition of the antigen A vary between and within the various subgroups of A, between single cells, and between the convex and concave parts of the cells.…”
mentioning
confidence: 99%